Psychometric properties of the Brazilian version of Clinical Perfectionism Questionnaire after rewording negatively keyed items - Rocha, Luiz Fellipe Dias da (2022)
The present study aims to verify the psychometric properties of the Brazilian version of Clinical Perfectionism Questionnaire after rewording negatively keyed items into positive (CPQ+). It was used a convenience sample of 168 Brazilian university students (M=25.37, SD=7.40), being 76.8% women. After rewording the negatively keyed items into positive, the CPQ+ was applied. The Depression, Anxiety and Stress Scales – Short Form (DASS-21) were also applied. The Corrected Item-Total Correlation values of CPQ+ items were close to or higher than the cutoff point. After exclusion of item 8, due to crossloading, and correlation between errors of items 3 and 10, the correlated two-factor model presented the best fit of latent structure to CPQ+, through Confirmatory Factor Analysis. The Perfectionistic Concerns dimension of CPQ+ was greater related to global score of DASS-21 in comparison to the Perfectionistic Striving dimension, indicating good validity regarding other variables. In summary, results recommend the use of CPQ+ presented in this study, it is, a version with 11 positive items.